Ageing response of Ni-rich NiTi shape memory alloy additively manufactured by electron beam freeform fabrication - R.P.M. Guimarães; B. Rauchdobler; F. Pixner; F.M.B. Ferraz; A. Mahdi; N. Enzinger; C. Poletti; S.T. Amancio-Filho (Journal of Materials Research and Technology)
Ni-rich NiTi alloys are known for their exceptional superelastic properties, but achieving consistent performance remains challenging with traditional methods. This study explores electron beam freeform fabrication (EBF3) to produce multitrack, multilayer NiTi structures and applies targeted thermal treatments to enhance thermo-mechanical properties. Results show that low dilution during EBF3 leads to structural imperfections, while optimised deposition yields regions of coarse columnar and equiaxed grains, Ni-rich precipitates (Ni4Ti3), and Ti-rich Ti4Ni2Ox structures. Solution treatment at 950 °C for 6 h increased the grain size, reduced the anisotropy of the equiaxed grains, dissolved Ni-rich precipitates, and refined Ti-rich structures, facilitating a one-step B2 ↔ B19' transformation. Variations in martensitic transformation temperature (Ms) along the building height reflected microstructural differences, amplified by heat treatment. Ageing at 350 °C and 450 °C for 1, 6, and 12 h promoted phase transformations with R-phase formation, with Ms decreasing at shorter ageing times but increasing as precipitates coarsened. The solubilised sample aged at 350 °C for 12 h showed optimal superelastic behaviour, with nearly complete strain recovery and minimal permanent strain (1.3%) after ten compression cycles under 860 MPa. This demonstrates the importance of processing parameter choice and post-thermal treatments in tailoring additively manufactured NiTi alloy performance, offering insights for practical applications.